The Stronghold on St. Peter’s Hill in Radom (Poland). Archaeology, Biography of the Place, and Practices of Memory - Trzeciecki, Maciej (Analecta Archaeologica Ressoviensia, 2018)
The stronghold called St. Peter’s hill in Radom is located in the centre of the city, in an area severely degraded by the side effects of 19th- and 20th-century industrialisation. The archaeological excavations and paleoecological research carried out in 2009–2013 created a background for studying its complex past and designing the future. The biography of St. Peter’s hill encompasses the early medieval power centre, late medieval urbanisation, nineteenth-century industrialisation, subsequent degradation of material and human resources, and present revitalisation projects. This place is far more than an archaeological site or even a part of archaeological heritage. It is a unique cultural landscape, which emerged as a result of long-lasting mutual relations between man and nature. Its materiality constitutes an inalienable cultural capital, indispensable for the reconstruction of local identities and communities of memory.